2014
DOI: 10.1039/c4sm01483a
|View full text |Cite
|
Sign up to set email alerts
|

Approach to universal self-similar attractor for the levelling of thin liquid films

Abstract: We compare the capillary levelling of a random surface perturbation on a thin polystyrene film with a theoretical study on the two-dimensional capillary-driven thin film equation. Using atomic force microscopy, we follow the time evolution of samples prepared with different initial perturbations of the free surface. In particular, we show that the surface profiles present long term self-similarity, and furthermore, that they converge to a universal self-similar attractor that only depends on the volume of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 48 publications
1
34
0
Order By: Relevance
“…and where we introduced the self-similar variable U = RT −1/4 . Note that the function φ can be written in terms of hypergeometric functions [31,52,54,58]. The solution to any summable initial perturbation Z(R, 0) = Z 0 (R) is simply given by the convolution (G * Z 0 )(R, T ).…”
Section: Theoretical Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…and where we introduced the self-similar variable U = RT −1/4 . Note that the function φ can be written in terms of hypergeometric functions [31,52,54,58]. The solution to any summable initial perturbation Z(R, 0) = Z 0 (R) is simply given by the convolution (G * Z 0 )(R, T ).…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…In that sense, the attractor functions are referred to as universal attractors. If volume is added to the reference flat film by the initial perturbation, M 0 = 0, the profile d(x, t) will converge to the function F 0 (u) in finite time [31]. If no volume is added by the initial perturbation, then the profile will converge to the first term with a non-zero prefactor in Eq.…”
Section: Casementioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that profiles following Eq. 2 are self-similar after a transient time [13,[32][33][34][35]. Fig.…”
mentioning
confidence: 99%
“…Thus we emphasize here that the collapse into a symmetric shape is a consequence of being in a deeply nonlinear regime. The linear regime of our problem is similar to another curvature-driven problem -that of the relaxation of a perturbed liquid-air interface [20,21] -in that they flow to attracting set of shapes at long times. We show this explicitly by simulating five different asymmetric initial-conditions each with a straight portion attached to a semi-circular portion as in fig.…”
Section: Asymmetric Initial Conditionsmentioning
confidence: 96%